Evaluation of the 2016 ENV57 MetroERM measurement comparison on 137Cs, 134Cs and 131I in air filters. (January 2019) - Altzitzoglou, Timotheos; Hult, Mikael; De Cort, Marc
Abstract: In 2016, the European Commission's Joint Research Centre organised an interlaboratory comparison exercise on the measurement of 137 Cs, 134 Cs and 131 I in air filters. The exercise was conducted in the frame of the MetroERM EMRP project with code ENV57. This paper describes the context of the interlaboratory measurement comparison, the technical implementation, the air filter measurements performed by the participating laboratories and finally the evaluation of the comparison results. The intercomparison exercise results are such that 56 out of the 67 laboratories (i.e. 84%) reported values within the ±20% range of the reference value for both the 137 Cs and 134 Cs. The evaluation of the performance of the laboratories on 131 I was complicated and the details are explained. Nevertheless, 20 (30%) laboratories reported results for 131 I with a percentage difference from the reference value within the ±20% range. Highlights: In 2016, the EC Joint Research Centre organised an interlaboratory comparison. The exercise was conducted in the frame of MetroERM EMRP project with code ENV57. 67 laboratories participated by measuring 137 Cs, 134 Cs and 131 I in air filters. 56 laboratories reported within ±20% from the reference value for 137 Cs and 134 Cs. Due to a complication, only 20 laboratories reported results within ±20% for 131 I.